Role of Neuroinflammation in Autism Spectrum Disorder and the Emergence of Brain Histaminergic System. Lessons Also for BPSD? - Eissa, Nermin; Sadeq, Adel; Sasse, Astrid; Sadek, Bassem (Frontiers in Pharmacology, 2020)
Many behavioral and psychological symptoms of dementia (BPSD) share similarities in executing functioning and communication deficits with those described in several neuropsychiatric disorders, including Alzheimer’s disease (AD), epilepsy, schizophrenia (SCH), and Autism spectrum disorder (ASD). Numerous studies over the last four decades have documented altered neuroinflammation among individuals diagnosed with ASD. The purpose of this review is to examine the hypothesis that central histamine (HA) plays a significant role in the regulation of neuroinflammatory processes of microglia functions in numerous neuropsychiatric diseases, including AD, SCH, BPSD, and ASD. In addition, this review summarizes the latest preclinical and clinical results that support the relevance of histamine H1-, H2-, and H3-receptor antagonists for the potential treatment of cognitive symptoms in ASD, SCH, AD, epilepsy and BPSD, based on the substantial symptomatic overlap between these disorders with regards to cognitive dysfunction. The review focusses on the histaminergic neurotransmission as relevant in these brain disorders, as well as the effects of a variety of H3R antagonists in animal models and in clinical studies.